Centralized Learning and Assessment Tool for Department of Education – Division of Laguna’s Araling Panlipunan Subjects - Mauricio, Jennilyn Q.; Cagayan, Keith Bryan I.; Serrano, James Russell M.; Balahadia, Francis F.; Sandoval, For-Ian V. (International Journal of Computing Sciences Research; Vol 1 No 2 (2017): Vol 1, No 2, 2017)
Purpose – This research project seeks to design, develop, and test the acceptability innovative e-learning management system to transform traditional methods into Information Communication and Technology (ICT) based approach, to improve the quality of education, enhance teachers’ teaching strategies, and to meet the demands of the 21st century teachers and learners as a result of the implementation of the K to12 ICT integration in Araling Panlipunan (AP). Method – The researchers conducted a series of surveys and interviews with the ICT heads, AP department heads, master teachers, and district supervisor. Questionnaires and literature were also employed to gather relevant information vital to planning, designing and development of a prototype. The design of the system is responsive to mobile and another portable device. The system development was divided in four phases: requirement planning, user design, construction or development and cutover. The developers used software development languages, such as HTML5 and PHP. The programmers employed MySQL database. In addition, other necessary software requirements were also used like internet browser, Notepad++, Adobe Dreamweaver, TinyMCE and XAMPP. Alpha and Beta testing were used to minimize the errors experienced by respondents. The result of system testing was analyzed descriptively using frequency, rank, and weighted mean. Results – The system was tested and evaluated using the ISO 9126 Evaluation Model to determine the acceptance level of the proposed system. The overall acceptance rating in terms of functionality, reliability, usability, efficiency, maintainability and portability is highly acceptable. It was a good indication that the developers met the necessary requirement of a learning management system by incorporating additional features. Conclusion –The goal of creating this alternative approach of teaching and evaluation process is to support teachers and students’ adaptation to e-learning and e-assessment. The study also achieved its goals to meet the demands of 21st century teachers and learners as a result of the implementation of K-12 curriculum through customized online-based responsive e-learning and e-assessment tool. These trends for Philippine education systems will empower the teachers and students to become more confident and competent in the use of technologies, shared resources, and collaborative learning. Recommendations –The system will bring new educational experiences to the young generations of both elementary teachers and students in particular to the DepEd-Division of Laguna. The system may be presented to the Department of Education for implementation as basis for creating e-learning tool not only for Araling Panlipunan but for all courses with more interactive and collaborative features in the system. Implications –The implementation of the said system is highly recommended to cope with the emerging trends of ICT in Education as a result of the implementation of the K to 12 programs. Furthermore, learning and assessment process can become more exciting and productive when ICT is being applied in public schools which can be a new student-centered assessment means to gauge learners and likewise recognize diverse learning styles.